PENINGKATAN MOTIVASI BELAJAR MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS VIII - Rofifah Rofifah; Sumargiyani Sumargiyani (Universitas Muhammadiyah Semarang, 2018)
The paper is wriTten due to the lack of motivation of second junior high school Muhammadiyah boarding school Pleret Yogyakarta students in even semester in 2017/2018. The purpose of the paper is to increase the motivation of students in learning mathematics with STAD learning method of The second junior high school Muhammadiyah boarding school Pleret Yogyakarta in even semester 2017/2018. The type of this observation is class action research that subject are the girl of second junior high school Muhammadiyah boarding school Pleret Yogyakarta students in even semester 2017/2018. The object of the research isthe mathematics learning process by applying STAD. The research did in two cycles. The instruments that used are the interview guidelines, observation guidelines, and questionnaires. Collecting data did by interview observation and questionnaires. The data analysis that used is data reduction, data display and trigunalsi. According to the research, it show that the learning motivation get increase from cycle I to cycle II. It showed by every aspect : diligent doing the assignment by students are 50% (enough) to 57% (enough), tenacious face the problem by the students are 53% (enough) to 57% (enough), like more working alone by students are 52% (enough) to 56% (enough), more get boring for daily assignments are 61% (high) to 63% (high), able to keep his opinion58% (low) to 70% (high)Keywords: STAD learning, learning motivation